KKN Membaca - Erbakan, Muhammad Ichsan; Haq, Muhammad Daffaul; Fajri, Bintang; Pratama, Dandy Anugrah; Arif, Hilda Meisya; Asnawati, Asnawati; Rulyanti, Merry; Martiani, Martiani; Maryaningsih, Maryaningsih; Narti, Sri; Nur’Aini, Hesti; Fariadi, Herri (LPPM Universitas Dehasen Bengkulu, 2025)
Kuliah Kerja Nyata (KKN) is one of the student community service programs at Dehasen University. In 2025, KKN emphasizes the development of student creativity as well as an understanding of the conditions and potential of the target community. One of the main issues raised is the low reading interest among students in Indonesia, which remains a serious problem despite the increasing access to information through technology. This research uses a descriptive method with a qualitative approach to describe the understanding of school community members regarding literacy and its implementation in teaching and learning activities in elementary schools. Data were collected through observation, interviews, and documentation to understand the phenomenon in depth. The research results show that the reading method, which involves asking students to read a text and retell its content, accompanied by the provision of rewards, effectively improves students' reading skills significantly. Students showed improvement in understanding the text, recognizing difficult words, and visualizing the content of the reading. In addition, this activity also successfully increased students' interest in reading, making them more motivated to read other books. Teachers reported an improvement in students' speaking and writing skills as a result of this activity. Thus, the reading program implemented through community service (KKN) has proven effective in improving students' academic abilities while also building a strong literacy culture.